2018
DOI: 10.1038/s41467-017-02553-6
|View full text |Cite
|
Sign up to set email alerts
|

Cryo EM structure of intact rotary H+-ATPase/synthase from Thermus thermophilus

Abstract: Proton translocating rotary ATPases couple ATP hydrolysis/synthesis, which occurs in the soluble domain, with proton flow through the membrane domain via a rotation of the common central rotor complex against the surrounding peripheral stator apparatus. Here, we present a large data set of single particle cryo-electron micrograph images of the V/A type H+-rotary ATPase from the bacterium Thermus thermophilus, enabling the identification of three rotational states based on the orientation of the rotor subunit. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
61
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 49 publications
4
61
1
Order By: Relevance
“…For Tth V/A-ATPase, acquisition of micrographs was carried out using a Titan Krios equipped with a Falcon II direct electron detector. Cryo-EM micrographs of the complexes reconstituted into nanodiscs resulted in higher resolution EM maps compared with the LMNG solubilized preparation previous reported ( 17 ). The strategy of single particle analysis for Tth V/A-ATPase is summarized in Figure S2A.…”
Section: Main Textmentioning
confidence: 68%
See 2 more Smart Citations
“…For Tth V/A-ATPase, acquisition of micrographs was carried out using a Titan Krios equipped with a Falcon II direct electron detector. Cryo-EM micrographs of the complexes reconstituted into nanodiscs resulted in higher resolution EM maps compared with the LMNG solubilized preparation previous reported ( 17 ). The strategy of single particle analysis for Tth V/A-ATPase is summarized in Figure S2A.…”
Section: Main Textmentioning
confidence: 68%
“…Structural analysis using cryogenic microscopy (cryoEM) of the holo V/A-ATPase, including our recent study, revealed several rotational states of the entire holo complex ( 17, 27 ). However, understanding of the inhibition mechanism of the isolated Tth V o is currently limited due to a lack of a high resolution structure.…”
Section: Main Textmentioning
confidence: 86%
See 1 more Smart Citation
“…(B) Models that correspond to three rotational states of one of the peripheral stalks of the V-ATPase of S. cerevisiae ; PDBs 3J9T, 3J9U, 3J9V from Zhao et al (2015) . (C) Models that correspond to three rotational states of one of the peripheral stalks of the A-ATPase of T. thermophilus ; PDBs 5Y5X, 5Y5Z, 5Y60 from Nakanishi et al (2018) . The black horizontal lines indicate the mitochondrial inner membrane.…”
Section: The Roles Of the Peripheral Stalkmentioning
confidence: 99%
“…The authors argue that this can be due to the fact that this enzyme has a larger rotational asymmetry (3:12) compared to the one of the yeast V-ATPase (3:10) and bovine F-ATPase (3:8), which may cause it to adopt an energetically favorable rotational state in which most of the images are obtained, resulting in an apparent lack of flexibility. Recently, a larger data set of single particle images obtained by Nakanishi et al (2018) allowed the identification of the missing third rotational state of the enzyme of T. thermophilus ; taken together, the structures show there is a dynamic rearrangement of the peripheral stalks in the transitions between each rotational state ( Nakanishi et al, 2018 ; Figure 7C ).…”
Section: The Roles Of the Peripheral Stalkmentioning
confidence: 99%